Needs Analysis: Development of Character-integrated Problem Solving Model for Chemistry Lessons in Senior High Schools - Mauliza Mauliza; Nurhafidhah Nurhafidhah; Joko Hariadi (Jurnal Penelitian Pendidikan IPA, 2022)
Problem-solving learning models can not only improve cognitive and psychomotor aspects but also affective aspects. One of the affective aspects is character. This study aims to analyze the needs as a basis for developing a character-integrated problem-solving model in high school. This study uses a survey method. The research population is all Senior High School (SMA) and chemistry teachers in Langsa city. The research sample was determined by purposive sampling technique, obtained 4 Senior high schools, along with 7 chemistry teachers. Data were collected by using questionnaires, observation, and interview techniques. The type of questionnaire used is an open-closed questionnaire, consisting of 30 questions. The specific indicators used to reveal the need for developing a character-integrated problem solving are teacher readiness, teacher's need, student’s need, and Support. Data were analyzed descriptively. The results show that the development of a character-integrated problem-solving model for chemistry lessons in senior high school is very much needed. The findings of this study are in accordance with the findings of previous studies